THE EFFECT OF MOTIVATION, THE ENVIRONMENT WORK AND THE LEADERSHIP PRINCIPAL’S ON TEACHER’S PERFORMANCE IN SMAN AMBULU - Haris Sutanto; Mohammad Dimyati; Agustin HP (MBA - Journal of Management and Business Aplication, 2018)
The effect of work motivation, environment work and principal leadership to the teacher performance in SMAN Ambulu. There are three problems in this research. They are 1) The work motivation effect partially to the teacher performance; 2) The work environment effect partially to the teacher performance; 3) The principal leadership affect partially to the teacher performance. The population used in this research were all of the teachers of SMAN Ambulu that consist of 56 teachers. The sum of sample needed in this research were 40 teachers. The data analysis method used experiment of doubled linier regression by using Microsoft Excel and SPSS program. The result of the research and data analysis shows that 1) the work motivation affect partially to the teacher’s performance significantly. The significant value of statistical variable work motivation is 0,02. So, its significant value is smaller than 0,05 or 0,002 < 0,05. 2) work environment affect partially to the teacher performance significant. The significant value of statistical variable work environment 0,000. So, its significant value is smaller than 0,05 or 0,000< 0,05. 3) The significant value of statistical variable of the principal leadership is 0,000. So, its significant value is smaller than 0,05 or 0,000< 0,05. The conclusion is that work motivation, work environment and the principal’s leadership can increase their performance significantly. Keyword : work motivation, work environment, principal leadership, and teacher performance